Evaluating state level transportation revenue alternatives. Issue 3 (September 2017) - Pulipati, Sasanka Bhushan; Mattingly, Stephen P.; Casey, Colleen
Highlights: Multi-criteria analysis is needed to select state level transportation revenue strategy. Evaluation criteria includes priorities of officials involved in revenue strategy selection. Alternatives assessment on individual criteria is based on earlier scientific studies. Outranking method, PROMETHEE I, is more suitable evaluation technique for this problem. Recommended strategy for Texas includes increasing fuel tax and tolling new highways. Abstract: Numerous studies have investigated the state of transportation funding in US states and forecasted a significant funding deficiency. Reasons for this include the lack of political will to increase the rates of fuel taxes, the loss in purchasing power of the fuel tax due to inflation, and the reduction in revenue due to increased use of alternative fuel vehicles. Possible options to generate the additional revenue to fill this funding gap range from modifying existing taxes and fees to implementing new revenue sources. However, determining what to do and offering policy recommendations can be challenging and may vary from jurisdiction to jurisdiction. The authors' critical review of the methods used by earlier studies that evaluate revenue generation strategies at the state level reveals a lack of systematic analysis. In response, the authors propose the use of a systematic multi-criteria analysis (MCA) as a better decision support tool. The MCA is argued to be an improvement over current methods because the best funding strategy depends not only on revenue generation but also on other parameters such as fairness and ease of implementation. To support the argument, the authors conduct a comprehensive multi-criteria evaluation of transportation revenue generation alternatives for the State of Texas. The authors' criteria system provides a better platform for including the priorities of stakeholders and policy makers at different levels. Including an outranking method such as PROMETHEE and a scenario analysis, the evaluation becomes more objective and more transparent. This enables the decision makers to more effectively compare the competing objectives of different alternatives. The authors discuss the drawbacks of the recent transportation funding decisions made by the Texas Legislature and highlight how the systematic evaluation can improve decision making. The authors recommend that states follow the systematic evaluation of funding options described in this paper, which can provide policy makers and the public a better understanding of the pros and cons of the funding options thereby helping them to select the most suitable funding strategy.